Technical and tactical skills related to performance levels in tennis: A systematic review - Kolman, N. S.; Kramer, T.; Elferink-Gemser, M. T.; Huijgen, B. C. H.; Visscher, C. (Journal of Sports Sciences, 2019)
The aim of this systematic review is to provide an overview of outcome measures and instruments identified in the literature for examining technical and tactical skills in tennis related to performance levels. Such instruments can be used to identify talent or the specific skill development training needs of particular players. Searches for this review were conducted using the PubMed, Web of Science, and PsycInfo databases. Out of 733 publications identified through these searches, 40 articles were considered relevant and included in this study. They were divided into three categories: (1) technical skills, (2) tactical skills and (3) integrated technical and tactical skills. There was strong evidence that technical skills (ball velocity and to a lesser extent ball accuracy) and tactical skills (decision making, anticipation, tactical knowledge and visual search strategies) differed among players according to their performance levels. However, integrated measurement of these skills is required, because winning a point largely hinges on a tactical decision to perform a particular stroke (i.e., technical execution). Therefore, future research should focus on examining the relationship between these skills and tennis performance and on the development of integrated methods for measuring these skills.